A novel domain decomposition-finite difference time domain method for composite scattering from a target above rough surface. Issue 2 (4th March 2021) - Tian, Wei; Wei, Bing; He, Xin-Bo
Abstract : A novel domain decomposition-finite difference time domain (DD-FDTD) method is proposed to improve the computation efficiency of the traditional finite difference time domain (FDTD) method in calculating composite scattering from a target above a rough surface. In this scheme, the target and the rough surface are placed into the target subdomain and the rough surface subdomain, respectively. The incident waves of the target subdomain, including the directly illuminated wave and the nonplanar reflected wave from the rough surface, are introduced by invoking the Huygens' principle and the equivalence principle. The FDTD method is executed in each subdomain to obtain the scattering fields of the target and the rough surface, and the scattering contribution of the rough surface from the reflected wave of target is taken into account. In comparison with the traditional FDTD method, the proposed method has significant advantages in saving memory usage and in reducing computation time, which is more efficient in solving the composite scattering problems with larger distance between target and rough surface.